2014
DOI: 10.1155/2014/905158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variable Thermal Conductivity on MHD Boundary Layer Slip Flow of Ethylene-Glycol Based Cu Nanofluids over a Stretching Sheet with Convective Boundary Condition

Abstract: An analysis is carried out to investigate the influence of variable thermal conductivity and partial velocity slip on hydromagnetic two-dimensional boundary layer flow of a nanofluid with Cu nanoparticles over a stretching sheet with convective boundary condition. Using similarity transformation, the governing boundary layer equations along with the appropriate boundary conditions are transformed to a set of ordinary differential equations. Employing Runge-kutta fourth-order method along with shooting techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Finally, Vw is the constant suction/injection velocity across the surface. Commonly used property relations for nanofluids are presented as (for details see [31][32][33]):…”
Section: Physical Model and Formulationmentioning
confidence: 99%
“…Finally, Vw is the constant suction/injection velocity across the surface. Commonly used property relations for nanofluids are presented as (for details see [31][32][33]):…”
Section: Physical Model and Formulationmentioning
confidence: 99%
“…Slip flow of Casson fluid with variable fluid physical property under radiation was studied by Poornima et al (2015). Bhaskar Reddy et al (2014) investigated the impact of variable thermal conductivity past a stretching sheet. Subba Rao et al (2016) studied the radiation effects past variable porosity with slip.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Following Maxwell [4], Bhaskar et al [34] and Arunachalam [42], the nanofluid's physical parameters are taken as:…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
“…Noghrehabadi et al [33] observed the effects of partial slip boundary conditions on the flow and heat transfer of nanofluids. Bhaskar et al [34] carried out an analysis to investigate the influence of variable thermal conductivity and partial velocity slip on the hydromagnetic two-dimensional boundary layer flow of nanofluids over a porous sheet with a convective boundary condition. Noghrehabadi et al [35] carried out a study on the effects of variable thermal conductivity and viscosity on the natural convective heat transfer of nanofluids over a vertical plate.…”
Section: Introductionmentioning
confidence: 99%